Moderate Reverberation Does Not Increase Subjective Fatigue, Subjective Listening Effort, or Behavioral Listening Effort in School-Aged Children - Picou, Erin M.; Bean, Brianna; Marcrum, Steven C.; Ricketts, Todd A.; Hornsby, Benjamin W. Y. (Frontiers in Psychology, 2019)
Background noise and reverberation levels in typical classrooms have negative effects on speech recognition, but their effects on listening effort and fatigue are less well understood. Based on the Framework for Understanding Effortful Listening, noise and reverberation would be expected to increase both listening effort and fatigue. However, previous investigations of the effects of reverberation for adults have resulted in mixed findings. Some discrepancies in the literature might be accounted for by methodological differences; behavioral and subjective indices of listening effort do not often align in adults. The effects of sustained listening on self-reported fatigue in school-aged children are also not well understood. The purposes of this project were to 1) evaluate the effects of noise and reverberation on listening effort in school-aged children using behavioral and subjective measures, 2) compare subjective and behavioral indices of listening effort, and 3) evaluate the effects of reverberation on self-reported fatigue. Twenty typically developing children (10 – 17 years old) participated. Participants completed dual-task testing in two rooms that varied in terms of reverberation, an audiometric sound booth and a moderately reverberant room. In each room, testing was completed in quiet and in two levels of background noise. Participants provided subjective ratings of listening effort after completing the dual-task in each listening condition. Subjective ratings of fatigue were completed before and after testing in each level of reverberation. Results revealed background noise, not reverberation, increased behavioral and subjective listening effort. Subjective ratings of perceived performance, ease of listening, and desire to control the listening situation revealed a similar pattern of results as word recognition performance, making them poor candidates for providing an indication of behavioral listening effort. However, ratings of time perception were moderately correlated with behavioral listening effort. Finally, sustained listening for approximately 25 minutes increased self-reported fatigue, although changes in fatigue were comparable in low and moderate reverberant environments. In total, these data offer no evidence that a moderate level of reverberation increases listening effort or fatigue, but the data do support the reduction of background noise in classrooms